Building an Online-Based Point of Sale Application at the Anton Store - Andika Septian Nugraha; Sapri Sapri; Arius Satoni Kurniawansyah (Penerbit Jurnal Indonesia, 2021)
Anton Bengkulu shop is a shop that sells goods and food for daily needs. So far, the processing process at the Anton Bengkulu Store has not used a computer for sales transactions, all of these processes are still using manual notebooks, and manual notes (data attached). This makes it difficult for the Anton Bengkulu Store to find out the availability of stock of goods and reports on the sale of goods at the Anton Bengkulu Store, because they have to calculate one by one the notes that have been issued and because there are also sales that do not use notes, so that it can cause losses and the stock of goods does not match the needs. which exists. The Online-Based Point Of Sale application at the Anton Store is an application that was built to make it easier for consumers to view and order products and shop at the Anton Store. This point of sale application can be accessed via the online link http://andika.vadapp.my.id so that it can be opened anytime and anywhere. This Point Of Sale application is made using the PHP programming language and MySQL database. This application displays information on products sold at the Anton Store, and there are 2 access rights applied to this application, namely administrator access rights and consumer access rights which have different functions. Based on the tests that have been carried out, the results show that the functionality of the Point Of Sale Application at the Anton Store runs as expected.